Археологічне вивчення Цецинського замку у висвітленні Чернівецької німецькомовної преси австрійської доби - Чучко, Михайло Костянтинович; Chuchko, Mykhailo (Археологія Буковини: здобутки та перспективи: Тези доповідей ІХ міжнародного наукового семінару (м. Чернівці, 19 грудня 2025 р.). – Чернівці: Технодрук, 2025., 2025)
The study of the past of Bukovina, in particular the history of the study of archaeological monuments of the region of the Middle Ages, remains a topical problem for local history studies. A special place among the late medieval monuments of the Upper Poprut is occupied by the castle of Cecino, the ruins of the defensive tower of which were preserved until 1959 on the top of the mountain of the same name, located on the western outskirts of Chernivtsi. This Moldavian castle was the administrative center of the Cecino "state" - a volost within the so-called "Shipynсi Land" - the northern border territory of the Moldavian Principality. Cecino is first mentioned in 1395, the last time - in 1456. After the decline of Cecino, the town of Chernivtsi, where the voivodeship customs office was located, became the administrative center of the volost in 1457. Publications of German-language Chernivtsi newspapers of the early 20th century provide valuable material on the organization and conduct of archaeological explorations at Cecino by Prof. V. Milkovich and the results he published.
Archäologische Untersuchungen der Burg Tsetsyn in der Berichterstattung der deutschsprachigen Presse von Czernowitz während der österreichischen Ära
ЧНУ
Keywords: Bukovina, Middle Ages, late medieval monuments, castle, Ceсina, Ceсina "state", Moldavian Principality.